Vulvar varicosities in pregnancy - concealed veins, unexpected complications: a rare case report - Chaturvedi, Pragya; Garude, Swapnali; Chavan, Niranjan N.; Gaekwad, Geetika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Vulvar varicosities are an uncommon manifestation of venous congestion during pregnancy, reported in 2-4% of pregnant women and usually resolving spontaneously after delivery.¹ Rarely, they may be associated with intrapartum or postpartum complications such as rupture and hematoma formation.³ We report a primigravida with unilateral vulvar varicosities presenting in active labor who underwent vaginal delivery with preventive intrapartum measures. Postpartum development of a vulvar hematoma required surgical evacuation, followed by imaging-guided conservative management⁶. The patient developed a postpartum vulvar hematoma requiring incision and drainage, blood component therapy, and close monitoring. Imaging demonstrated a residual organized hematoma with extensive vulvovaginal varicosities and no active arterial bleeding. Conservative management resulted in gradual resolution and complete recovery. Vulvar varicosities are not an absolute contraindication to vaginal delivery; however, vigilant postpartum surveillance is essential. Early recognition and timely intervention can prevent significant maternal morbidity.